No altar e na sala de aula : vestígios da catequese e educação franciscanas no sudeste goiano (1944-1963) - Barros, Aparecida Maria Almeida (2010)
The survey, whose object throve institutional relations of church and society mediated by education, aimed to examine the remains of catechesis and education materialized in the Franciscan parish schools established in Goias in the first half of the twentieth century. These institutions intregraram Franciscan missionary project of two American religious orders: the Friars Minor (1944) and the Sisters of Allegany (1946). The theoretical assumptions of cultural studies and historical research located in the field of educational institutions guided search fundamentals. The research methodology documentation, which was essentially the basis for the analysis of empirical data. The specific object of catechesis, education and society, had the contribution of sociological theory and historical interpretation for the variables of social and economic context in which they entered the missionary and educational analyzed. Among the findings from the route and analysis, remains indicated that the Catechesis and Education Taught at the altar and in the classroom, they would have supported the project of evangelization and sacralization, strengthening the movement for renewal of the Roman Church and the new Christianity in Brazil . Uniquely, the consolidation of the Franciscan missionary work led to the syncretism of religious practices and the likely eclecticism of pedagogical practices and school strongly marked by active methods, in contrast to the structure and format of traditional religious order. The originality with the Franciscans not only spread their missionary project also defined as agreements and mediations with local realities, through the educational and catechetical work, resulted in the demarcation of spaces and competitors alike and the coexistence of the diverse.